Microorganisms in Biorefineries - Kamm, Birgit (Microbiology Monographs,, 2015)
The book describes how plant biomass can be used as renewable feedstock for producing and further processing various products. Particular attention is given to microbial processes both for the digestion of biomass and the synthesis of platform chemicals, biofuels and secondary products. Topics covered include: new metabolic pathways of microbes living on green plants and in silage; using lignocellulosic hydrolysates for the production of polyhydroxyalkanoates; fungi such as Penicillium as host for the production of heterologous proteins and enzymes; bioconversion of sugar hydrolysates into lipids; production of succinic acid, lactones, lactic acid and organic lactates using different bacteria species; cellulose hydrolyzing bacteria in the production of biogas from plant biomass; and isoprenoid compounds in engineered microbes.